TINGKAT PENGUNGKAPAN ISLAMIC SOCIAL REPORTING PADA BANK UMUM SYARIAH - Nitia Wijaya; M. Rasuli; Rofika Rofika (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2020)
This study aims to examine the effect of Sharia Governance Structure (IG Score, Investment Account Holder, and Size) and Profit on Islamic Social Reporting Disclosures at Islamic Public Banks in Indonesia. The study is a quantitative study that uses secondary data that is sourced from financial reports on Islamic banks listed on the Financial Services Authority (OJK) and the Indonesia Stock Exchange (IDX). Data were then analyzed using panel data regression analysis techniques through Eviews 9 software to test the relationship of hypotheses in this study. The result showed that shari’a governance structure has a positive effect on level of ISR disclosure. And the result also showed that profitability has a positive effect on level of ISR disclosure